The CJEU and the International Private Law. Facing the digitalization of goods and services - Michinel Álvarez, Miguel-Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Abstract: Faced with the problems that may arise when it comes to articulating community freedoms within the framework of the internal market for goods and services affected by the growing and unstoppable process of digitization, private law, for its part, responds with new rules that, each time with greater intensity, they unify aspects where there are discrepancies between the systems of the different Member States. But, given the clearly cross-border dimension of the type of existing relationships, the existing EU private international law acquis retains an important function, fine-tuned by the CJEU, on the path towards the establishment of a European digital sovereignty. This paper examines, from the perspective of this jurisprudence, the most relevant advances, from the perspective of liability, both contractual and non-contractual, related to that market.